The impact of climate variability on diarrhea incidence in Surakarta City, Indonesia 2021-2022 - Nurhayatun Evi; Ulfia Mila; Redhono Harioputro Dhani (BIO Web of Conferences)
Diarrhea is still a serious public health problem and an endemic disease in Indonesia, with the potential for outbreaks that frequently result in mortality. According to 2018 Primary Health Research data, the incidence of diarrhea in Indonesia was 6.8% for all ages and 11% for toddlers. Diarrhea is one of the diseases associated with climate variability. The goals of this study is to analyze the impact of climate variability (air temperature and humidity) on the incidence of diarrhea cases in Surakarta City from 2021 to 2022. This study use a cross-sectional method. The data used is secondary data from Surakarta City Statistics Center. The Pearson statistical test was used to analyze the differences between variable. The results of this study showed that air temperature (p = 0.01 and r = 1,000) and humidity (p = 0.01 and r = 1,000) have an impact on the incidence of diarrhea. In conclusion, temperature and humidity had a positive correlation with diarrhea cases.